High Tourniquet Failure Rates Among Non-Medical Personnel Do Not Improve with Tourniquet Training, Including Combat Stress Inoculation: A Randomized Controlled Trial. Issue 3 (2nd May 2019) - Tsur, Avishai Michael; Binyamin, Yaara; Koren, Lena; Ohayon, Sharon; Thompson, Patrick; Glassberg, Elon
Abstract: Background: The rate of failing to apply a tourniquet remains high. Hypothesis: The study objective was to examine whether early advanced training under conditions that approximate combat conditions and provide stress inoculation improve competency, compared to the current educational program of non-medical personnel. Methods: This was a randomized controlled trial. Male recruits of the armored corps were included in the study. During Combat Lifesaver training, recruits apply The Tourniquet 12 times. This educational program was used as the control group. The combat stress inoculation (CSI) group also included 12 tourniquet applications, albeit some of them in combat conditions such as low light and physical exertion. Three parameters defined success, and these parameters were measured by The Simulator: (1) applied pressure ≥ 200mmHg; (2) time to stop bleeding ≤ 60 seconds; and (3) placement up to 7.5cm above the amputation. Results: Out of the participants, 138 were assigned to the control group and 167 were assigned to the CSI group. The overall failure rate was 80.33% (81.90% in the control group versus 79.00% in the CSI group; P value = .565; 95% confidence interval, 0.677 to 2.122). Differences in pressure, time to stop bleeding, or placement were not significant (95% confidence intervals, −17.283 to 23.404, −1.792 to 6.105, and 0.932 to 2.387, respectively). Tourniquet placement was incorrect in most of the applications (62.30%). Conclusions: This study found high rates of failure in tourniquet application immediately after successful completion of tourniquet training. These rates did not improve with tourniquet training, including CSI. The results may indicate that better tourniquet training methods should be pursued. Tsur, AM, Binyamin, Y, Koren, L, Ohayon, S, Thompson; P, Glassberg, E. High tourniquet failure rates among non-medical personnel do not improve with tourniquet training, including combat stress inoculation: a randomized controlled trial. Prehosp Disaster Med. 2019;34(3):282–287.